The Challenge Of Islamic Education Teachers In The Milenial Era - Marini Nasution; Ali Yukla Adnin; Melati Chamariah (Proceeding International Seminar of Islamic Studies, 2019)
The rapid development of technology and information makes teachers need to be more extra draining their energy and mind to present learning in accordance with the needs of their time. If not the millennial era would be a new challenge for all teachers including Islamic religious education teachers, which so far have been perceived by students as being inattentive to this era.this paper aims to analyze: (1) students' perceptions about PAI teachers in the millennial era, (2) characteristics of PAI teachers in the millennial era, (3) PAI teacher challenges in the Millennial Era. This study uses qualitative research methods using a descriptive analysis approach. Data collection techniques are done by observation, interviews, and study documentation. This research was conducted at SMPIT Al-Munadi Medan, for 2 months, and with a total of 15 informants, and 3 teachers in Islamic religious education studies. The results showed that: (1) Students perceive that PAI teachers in the millennial era are teachers who have the ability to instil faith, devotion and good morals, teachers who master learning technology, teachers whose learning is based on innovation and life skills learning, (2 ) Characteristics of PAI teachers in the millennial era include being open with new information, happy with challenges and innovations, happy with creativity, flexible in learning, responding with changing times. (4) Reorientation of religious functions for students, secular, radical, and liberal understanding, low competence in the field of teacher technology, lack of understanding of the developmental psychology, culture and lifestyle of foreigners.